Sagot :
x=2 için 0 = 2 -5*0 +m burdan m m=-2 gelir
sonrada P(1) istedği için x yerine 1 yazacaksın
-1.p(1) = 2-5-2 cevap +5 yapar.
P(1)deki 1'i x'lerinyerine yazıyoruz
(1-2).P(1)=2-5+m
-1.P(1)=m-3
-1.P(1)=m-3
--------------
-1
p(1)=-m+3
Arkadaşım ben açıkladım ama yanlış olabilirsen yinede bi bak
Thank you for visiting our website wich cover about Matematik. We hope the information provided has been useful to you. Feel free to contact us if you have any questions or need further assistance. See you next time and dont miss to bookmark.